Nutritive value of eight hybrid sorghum grains and three hybrid corns compared in all-concentrate rations, Part I: Hybrid sorghum and corn characteristics and methods used to nutritionally evaluate them - R.L. McCollough (Kansas Agricultural Experiment Station Research Reports, 1972)
In 1971, Kansas produced 234 million bushels of sorghum grain worth $217,000,000, second only to Texas. Most of it is used as an energy source in livestock rations. Since the introduction of hybrid sorghum grain in 1956, yield has increased 25%.
Keywords: Cattlemen' s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Hybrid sorghum grains; Hybrid corn